Effect of the timing of force application on the toe trajectory in the swing phase for a wire-driven gait assistance robot - Tamon MIYAKE (The Japan Society of Mechanical Engineers, 2018)
We propose an effective timing of intermittent force application by a gait assistance robot with a wire-driven system to increase the toe trajectory throughout the swing phase. We tested different timings of force application at the shank, employing the short-term assistance of the robot to increase toe clearance throughout the swing phase. The force was applied to the shank to generate knee flexion torque because the shank motion generated by the knee flexion motion makes the largest contribution to toe clearance. Four timings of the force application were considered: when starting knee flexion before toe-off, when lifting the foot, while maintaining knee flexion after toe-off, and when finishing knee flexion after toe-off. Furthermore, we evaluated changes in the toe trajectory and articular angles of the lower limb for each timing condition. We used a timing detection method for the robot conducting tensile force control based on information from the hip, knee, and ankle angles. For all participants, an increase in the knee flexion angle in the early swing phase due to the force application increased the toe clearance throughout the swing phase. We thus conclude that force application when the user begins lifting their toe is effective in increasing toe clearance throughout the swing phase.